Global Value Chains and the Governance of 'Embedded' Food Commodities: The Case of Soy. (27th November 2018) - Heron, Tony; Prado, Patricia; West, Chris
Abstract: In recent decades, soy has emerged as one of the world's most significant food‐related commodities and is strongly linked to deforestation and habitat loss, especially in Latin America. However, only a very small proportion of soy is consumed directly as food by humans with the rest crushed to produce animal feed, oils, biofuel and other industrial products. We argue that the peculiar (but not necessarily unique) structural and institutional characteristics of the soy supply chain raises crucial questions about the promotion of sustainability in complex, non‐consumer facing global value chains (GVCs). The particular way that soy is 'embedded' in the food system has meant that consumer‐facing firms have been shielded from the externalities of its production and trade to a much larger degree than is the case for comparable food commodities. This, in turn, helps to explain the widely perceived inadequacies of the private certification of 'sustainable soy' – and ongoing and wider political struggles around land, labour and the environment – for more comprehensive and inclusive forms of governance. Abstract : There is a striking parallel between the analytical challenges that soy poses for researchers seeking to understand the drivers of soy production (and hence deforestation and habitat loss) and the practical difficulties that retailers have in accessing the data necessary to inform their own commitments to ethical sourcing.